2017
DOI: 10.2736/jjvd.23.5
|View full text |Cite
|
Sign up to set email alerts
|

CD3+ and Pax5+ Lymphocytes in the Dermis of Normal Skin from the Dorsolateral Thorax of Cats

Abstract: Very small numbers of resident T-lymphocytes are present in the dermis of normal skin of humans, cattle, sheep, dogs, and alpacas. The objective of this study was to determine the prevalence of lymphocytes, CD3+ cells (T-lymphocyte), and Pax5+ cells (B-lymphocyte) in the dermis of normal cat skin. Skin-biopsy specimens from the normal skin of the dorsolateral thorax from 29 cats were examined immunohistochemically for the presence of CD3+ and Pax5+ cells in the superficial and deep dermis. Two CD3+ lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It is interesting to note that in domestic veterinary species significant numbers of resident dermal lymphocytes have only been described in large animal species including cattle 14) , sheep 10) , alpacas 6) , and horses 13) . Similar studies in cats 8) and dogs 5) have reported only rare dermal lymphocytes in few animals.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…It is interesting to note that in domestic veterinary species significant numbers of resident dermal lymphocytes have only been described in large animal species including cattle 14) , sheep 10) , alpacas 6) , and horses 13) . Similar studies in cats 8) and dogs 5) have reported only rare dermal lymphocytes in few animals.…”
Section: Discussionsupporting
confidence: 71%
“…Resident dermal and epidermal T lymphocytes are a component of the skin immune system (SIS) in humans 2, 21) and mice 23) . This is probably also true in other domestic species in which resident dermal and epidermal lymphocytes have been detected 3,6,8,10,13,14) .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations